The primarly overlooked scaphoid fracture–a diagnostic challenge? Die primär nicht nachweisbare Skaphoidfraktur–Eine diagnostische Herausforderung? - Jungbluth, Pascal; Hakimi, M.; Windolf, J.; Schaedel-Hoepfner, M.; Betsch, Marcel (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2010)
INTRODUCTION: Scaphoid fractures represent the most common carpal bone fractures. These fractures may be overlooked due to insufficient diagnostics and lead to non-union and disability. A standardized diagnostic procedure with X-ray examinations, CT scans and/or MRI is recommended. We report on a case where a scaphoid fracture was overlooked, probably because of an incorrect technique of the computed tomography. CASE REPORT: A 42-year-old man was admitted to our emergency room after a fall on the out-stretched wrist. X-rays showed no evidence of a bony lesion. In the follow-up examination on the next day, a scaphoid fracture was still suspected clinically. Because of that a CT scan in thin slice technique with axial layers and multiplanar reconstruction was performed but showed no sign of a fracture. Six weeks after the trauma the patient presented with persistent wrist pain. X-rays and a CT scan of the wrist now demonstrated an old waist fracture of the scaphoid. -Operative treatment with iliac crest bone grafting and screw fixation was performed. DISCUSSION: Early diagnosis and a correct description of the fracture pattern are of high value in the treatment of scaphoid fractures. X-rays combined with a CT scan or an MRI scan of the affected wrist are considered as the diagnostic standard. The reported case demonstrates that even with a thin thickness layer CT scan in axial planes, a scaphoid fracture can be overlooked. Therefore we recommend after primarily inconspicuous X-rays a CT scan with primary -oblique-sagittal layers in the longitudinal axis of the scaphoid. If this shows no fracture and the clinical suspicion persists, an MRI scan should be performed. Georg Thieme Verlag KG Stuttgart, New York.
CRIS-Team Scopus Importer:2022-07-20